2006
DOI: 10.1002/chem.200600026
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Amplification by Kinetic Resolution Using A Racemic Reagent: Example in Amine Acetylation

Abstract: The reaction of a racemic reagent on a mixture of enantiomers with small ee (ee=enantiomeric excess) has been studied for amine acylation. A substantial asymmetric amplification could be realized, for example, from 67 to >95.5 ee. The combination of asymmetric amplifications is subsequently discussed. Two sequential asymmetric amplifications, one using a racemic reagent and another using a positive nonlinear effect allowed us to start from 1.5 % ee and end with a large amount of a product of 97 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…This nonlinear effect confirms that the oligomeric species Ca[3 a R ] n are the active catalysts, rather than the Ca II -free phosphoric acid or mono(phosphate) salt. [19,20] This remarkably strong negative linear effect may be explained with the ML n model of [23d,24,25] in which there is an equilibrium with homochiral and heterochiral adducts exhibiting different catalytic activity. Therefore, according to this model, the nonlinear effects resulted from the formation of the heterochiral dimer complexes Ca[3 a RS ] n over the homochiral adducts (Ca[3 a R ] n and Ca[3 a S ] n ); the heterochiral complexes are much more reactive than the homochiral complexes in forming the racemic 5 a (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…This nonlinear effect confirms that the oligomeric species Ca[3 a R ] n are the active catalysts, rather than the Ca II -free phosphoric acid or mono(phosphate) salt. [19,20] This remarkably strong negative linear effect may be explained with the ML n model of [23d,24,25] in which there is an equilibrium with homochiral and heterochiral adducts exhibiting different catalytic activity. Therefore, according to this model, the nonlinear effects resulted from the formation of the heterochiral dimer complexes Ca[3 a RS ] n over the homochiral adducts (Ca[3 a R ] n and Ca[3 a S ] n ); the heterochiral complexes are much more reactive than the homochiral complexes in forming the racemic 5 a (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The authors proposed a revised mechanism which is in agreement with the absence of a nonlinear effect. In 2002, we reported that the Ohno−Kobayashi protocol led to a strong asymmetric amplification, and recently, we used this protocol in a sequential combination of two asymmetric amplifications; the mechanistic implications were shortly discussed . We wish to report here that the asymmetric amplification associated to the Ohno−Kobayashi procedure is correlated with the insolubility of catalyst precursor 3a in toluene.…”
mentioning
confidence: 89%
“…His Review on nonlinear effects in asymmetric synthesis is considered seminal 2a. He recently described in Chemistry – A European Journal asymmetric amplification by kinetic resolution using a racemic reagent, with amine acetylation as an example 2b…”
Section: Awarded…︁mentioning
confidence: 99%